IDENTIFICATION OF CERTAIN DIFFUSE POROUS TREE SPECIES ACCORDING TO QUANTITATIVE INDICATORS OF THEIR ANATOMICAL ELEMENTS - Bardarov, Nikolai; Mladenova, Diyana (Innovation in Woodworking Industry and Engineering design, 2014)
In spite of the different diameter and density of the vessels of diffuse porous species, they can be more or less similar in these characteristics. This study discusses the differences of the vessels in several Bulgarian local growing tree species which have only single row core rays.There are measured the average diameter and density of the vessels. Using them, the area of the individual anatomical components is calculated. The mean and the variance are deter-mined in order to be used as diagnostic indicators. An examination of the statistical significance of the samples is made in order to determine which of the anatomical features can be used to identify the wooden species.